(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Financial inclusion is defined as a strategy to provide basic financial services to all members of society without considering their income or savings. The main goal of financial inclusion is to give the economically disadvantaged members of society trustworthy financial options without subjecting them to unfair treatment. Together, the governments of Tamilnadu and India launched a number of programs to support women who want to start their own businesses. However, in order to guarantee that the disadvantaged individuals continue to benefit, these programs must be regularly monitored. The survey may determine how aware consumers are of programs designed to support women who want to start their own businesses. The goal of this study is to gauge the awareness of incentive programs among female entrepreneurs. A primary source was utilized to gather data from 550 respondents, and the interview schedule was employed in this process. Data has been analyzed and interpreted using SPSS 20. Chi-square analysis, ANOVAs, and the T-test have all been applied. The findings of the study indicate that women entrepreneurs are not fully aware of the programs designed to encourage them to pursue entrepreneurial endeavors; therefore, in order to raise awareness, the government and financial institutions should host various workshops and seminars.